Reputation: 1888
The following Agda code:
module test where
open import Data.Float
import Relation.Binary.PropositionalEquality as Eq
open Eq using (_≡_)
open Eq.≡-Reasoning using (begin_; _≡⟨⟩_; step-≡; _∎)
postulate
distrib : {m a b : Float} → m * (a + b) ≡ (m * a) + (m * b)
dbg : (m a b : Float) → m * (a + b) ≡ (m * a) + (m * b)
dbg m a b =
begin
m * (a + b)
≡⟨ distrib ⟩ -- (Line "22")
(m * a) + (m * b)
∎
yields:
_m_18 : Float [ at /Users/dbanas/Documents/Agda/agda_misc/test.agda:22,6-13 ]
_a_19 : Float [ at /Users/dbanas/Documents/Agda/agda_misc/test.agda:22,6-13 ]
_b_20 : Float [ at /Users/dbanas/Documents/Agda/agda_misc/test.agda:22,6-13 ]
———— Errors ————————————————————————————————————————————————
Failed to solve the following constraints:
(_m_18 * _a_19) + (_m_18 * _b_20) = (m * a) + (m * b) : Float
_m_18 * (_a_19 + _b_20) = m * (a + b) : Float
after I type C-c C-l
.
(Note: "22,6-13" identifies the second occurrence of the word "distrib".)
I don't understand why the constraints can't be met. They seem trivially solvable:
_m_18 = m
_a_19 = a
_b_20 = b
Upvotes: 3
Views: 130
Reputation: 18587
While those solutions are correct, they're not inevitable, because multiplication and addition are not injective. In this case, you can fill in just m
in line 22, ie distrib {m = m}
.
Upvotes: 3